2021
DOI: 10.21831/economia.v17i2.39682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Board of Commissioners in Islamic Social Reporting

Abstract: This research aims to investigate how the board of commissioners plays a role in influencing Islamic social reporting. The object of this study was the disclosure of Islamic social reporting in sharia banking in Indonesia, through secondary data. Data were analyzed using multiple linear regression analysis. The findings showed the role of the board of commissioners in influencing the extent of Islamic social reporting disclosure more likely through the size of the board of commissioners, not through an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
3
2
Order By: Relevance
“…The existence of the Board of Commissioners is expected to encourage good supervision, especially during the Islamic banking development era. This study result contradicts the results of the studies conducted by Ifada et al (2021) and Indrawaty and Wardayati (2016) which suggest that the Board of Commissioners has an effect on ISR. However, this study aligns with the research of Lidyah et al (2019) which argues that the size of the Board of Commissioners has no effect on ISR.…”
Section: Board Of Commissioners Independent Commissioners Frequency O...contrasting
confidence: 99%
See 3 more Smart Citations
“…The existence of the Board of Commissioners is expected to encourage good supervision, especially during the Islamic banking development era. This study result contradicts the results of the studies conducted by Ifada et al (2021) and Indrawaty and Wardayati (2016) which suggest that the Board of Commissioners has an effect on ISR. However, this study aligns with the research of Lidyah et al (2019) which argues that the size of the Board of Commissioners has no effect on ISR.…”
Section: Board Of Commissioners Independent Commissioners Frequency O...contrasting
confidence: 99%
“…Therefore, the second hypothesis which states that independent commissioners have a positive effect on ISR is not supported. This study is aligned with the research conducted by Ifada et al (2021) which found that independent commissioners had no effect on ISR. However, this study contradicts the research of Sulistyawati and Indah (2017) which shows that independent commissioners have a positive effect on ISR disclosure.…”
Section: Board Of Commissioners Independent Commissioners Frequency O...supporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the research by Ifada et al (2021) and Aisyah et al (2022) sheds light on the role of the board of commissioners in influencing Islamic social reporting and financial performance in Islamic banks. The expertise and composition of the board of directors are crucial factors in enhancing financial performance and ensuring adherence to Islamic ethical standards.…”
Section: Islamic Structure Of the Board Of Commissioners And Directorsmentioning
confidence: 99%